Pengaruh Pertumbuhan Perusahaan Dan Likuiditas Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di BEI Tahun 2020-2024 - Anisa Yolanda Putri; Berta Agus Petra; Nila Pratiw (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of company growth and liquidity on company value with profitability as an intervening variable in food and beverage subsector companies listed on the Indonesia Stock Exchange for the period 2020-2024. The research method uses a quantitative approach with purposive sampling technique which resulted in 30 sample companies with a total of 150 observations. The data analysis technique uses multiple linear regression analysis and path analysis with SPSS version 26. The results show that: (1) company growth has a positive and significant effect on profitability (sig. 0.006 < 0.05); (2) liquidity has a positive and significant effect on profitability (sig. 0.000 < 0.05); (3) company growth has no significant effect on company value (sig. 0.529 > 0.05); (4) liquidity has a negative and significant effect on company value (sig. 0.020 < 0.05); (5) profitability has a positive and significant effect on company value (sig. 0.000 < 0.05); (6) profitability is able to mediate the effect of company growth on company value with indirect effect (0.137) greater than direct effect (-0.048); (7) profitability is able to mediate the effect of liquidity on company value with indirect effect (0.346) greater than direct effect (-0.203). The coefficient of determination (R²) shows that profitability is influenced by company growth and liquidity by 30.7%, while company value is influenced by company growth, liquidity, and profitability by 32.3%. This study confirms the importance of profitability as a mechanism linking company growth and liquidity to company value, and provides managerial implications that companies need to optimize asset and liquidity management to increase profitability which ultimately impacts on increasing company value.